2020
DOI: 10.1016/j.jaci.2020.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of asthma in hospitalized and nonhospitalized patients with COVID-19

Abstract: Background: The Centers for Disease Control and Prevention advises that patients with moderate to severe asthma belong to a high-risk group that is susceptible to severe coronavirus disease 2019 (COVID-19). However, the association between asthma and COVID-19 has not been well-established. Objective: The primary objective was to determine the prevalence of asthma among patients with COVID-19 in a major US health system. We assessed the clinical characteristics and comorbidities in asthmatic and nonasthmatic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
270
3
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(315 citation statements)
references
References 26 publications
27
270
3
15
Order By: Relevance
“… 9 - 11 A study conducted by Chiba et al evaluated 1526 PCR confirmed Covid positive patients and found that 220 (14%) of patients had comorbid asthma. 12 However, comorbid asthma was not found to increase risk of hospitalization in this study population. 12 Recent data released from the Center for Disease Control and Prevention evaluated COVID-19 positive patients from several hospitals throughout the United States and showed that 27.3% of COVID-positive inpatients aged 18 to 49 years listed asthma as a comorbidity, with an incidence of 8.9% in the general population.…”
Section: Does Asthma Increase the Risk Of Covid-19 Infection (See contrasting
confidence: 53%
See 1 more Smart Citation
“… 9 - 11 A study conducted by Chiba et al evaluated 1526 PCR confirmed Covid positive patients and found that 220 (14%) of patients had comorbid asthma. 12 However, comorbid asthma was not found to increase risk of hospitalization in this study population. 12 Recent data released from the Center for Disease Control and Prevention evaluated COVID-19 positive patients from several hospitals throughout the United States and showed that 27.3% of COVID-positive inpatients aged 18 to 49 years listed asthma as a comorbidity, with an incidence of 8.9% in the general population.…”
Section: Does Asthma Increase the Risk Of Covid-19 Infection (See contrasting
confidence: 53%
“… 12 However, comorbid asthma was not found to increase risk of hospitalization in this study population. 12 Recent data released from the Center for Disease Control and Prevention evaluated COVID-19 positive patients from several hospitals throughout the United States and showed that 27.3% of COVID-positive inpatients aged 18 to 49 years listed asthma as a comorbidity, with an incidence of 8.9% in the general population. 13 , 14 Although studies have shown higher rates of comorbid asthma in COVID-19 positive patients, it was not specified whether asthma was allergic or non-allergic in origin.…”
Section: Does Asthma Increase the Risk Of Covid-19 Infection (See contrasting
confidence: 53%
“…It has been reported that patients with asthma have reduced susceptibility to SARS-CoV-2, and that asthma symptoms are not exacerbated by SARS-CoV-2 infection [43][44][45] . However, it has been suggested that a subset of asthma patients (Type-2 low asthmatics) who are more at risk of SARS-CoV-2 show higher ACE2 expression in bronchial epithelium, associated with upregulation of viral response genes 46 .…”
Section: Short and Long Ace2 Are Regulated Differently In Severe Asthmamentioning
confidence: 99%
“…COPD) in populations studied, conditioning on patients who were hospitalized with COVID-19, 18 and/or not accounting for secular changes in COVID-19 testing criteria. 20 Our study improves upon these prior studies by rigorously defining asthma, excluding those with non-asthma chronic pulmonary conditions (i.e. COPD, CF, and ILD) who appear to be higher risk of severe COVID-19 outcomes with the risk being primarily driven by COPD, 21,22 and matching by PCR testing date.…”
Section: Discussionmentioning
confidence: 84%